Improving Students Pronunciation Using Video Dubbing (A Classroom Action Research for Tenth Grade and Eleventh Grade Students of Vocational High School) - Pamungkas, Firdaus Ditya (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2019)
This research aims to find out the impact of video dubbing on improving students’ speaking pronunciation. This research was applied for the tenth grade and eleventh grade of Vocational High School in Madiun city, province of East Java, Indonesia. The subject of the research consisted of 20 students, 14 female students and 6 male students. In collecting the data, researcher used observation to observe the implementation of video dubbing during teaching learning process and used test to find the improvement of students’ speaking pronunciation during the implementation of video dubbing. The research was conducted in two cycles, where each cycle consisted of 4 meetings. The research findings showed that the implementation of video dubbing could improve students’ speaking pronunciation. It can be concluded that the implementation of video dubbing in learning process has beneficial effect on students’ speaking skill, especially in pronunciation. Keywords: video dubbing, teaching speaking, pronunciation.